2016
DOI: 10.1111/cdev.12487
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Maternal Stress Predicts Methylation of Genes Regulating the Hypothalamic–Pituitary–Adrenocortical System in Mothers and Newborns in the Democratic Republic of Congo

Abstract: Exposure to stress early in life permanently shapes activity of the hypothalamic-pituitary-adrenocortical (HPA) axis and the brain. Prenatally, glucocorticoids pass through the placenta to the fetus with postnatal impacts on brain development, birth weight, and HPA axis functioning. Little is known about the biological mechanisms by which prenatal stress affects postnatal functioning. This study addresses this gap by examining the effect of chronic stress and traumatic war-related stress on epigenetic changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
155
1
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 177 publications
(178 citation statements)
references
References 61 publications
(86 reference statements)
8
155
1
5
Order By: Relevance
“…Previously, we reported that war traumas had stronger associations than chronic stress with methylation of genes regulating the HPA axis [57]. Here, we add to the literature on stress and epigenetics by showing that more severe war traumas also are more strongly related than chronic stress to methylation in a key gene regulating neuronal and placental development.…”
Section: Discussionsupporting
confidence: 52%
“…Previously, we reported that war traumas had stronger associations than chronic stress with methylation of genes regulating the HPA axis [57]. Here, we add to the literature on stress and epigenetics by showing that more severe war traumas also are more strongly related than chronic stress to methylation in a key gene regulating neuronal and placental development.…”
Section: Discussionsupporting
confidence: 52%
“…Kertes et al 16 , realizaron un estudio en la República Democrática del Congo en madres sometidas a estresores crónicos relacionados con la guerra durante la gestación de sus hijos. Al obtener muestras de sangre materna, de cordón umbilical y de placenta, verificaron que el estrés crónico y los traumas de guerra tuvieron efectos significativos sobre los sitios de unión de todos los factores transcripcionales estudiados relacionados con el eje HHA, demostrando que el EP impactó de manera diferente al tejido materno y fetal, lo que apoya el modelo que propone que el impacto del estrés varía en función de la fase vital.…”
Section: Otros Mecanismos Epigenómicosunclassified
“…Investigaciones en roedores 9 han corroborado que la exposición a condiciones adversas en la vida temprana podrían provocar alteraciones neuroendocrinas y metabólicas permanentes, repercutiendo en la dimensión conductual del individuo. En relación a esto, han recibido especial atención a nivel funcional el eje hipotalámico-hipofisiarioadrenal (HHA), los sistemas serotoninérgico, glutamatérgico, GABAérgico, y a nivel morfoló-gico, estructuras centrales corticales (e.g., corteza prefrontal, temporal, insular) 10 , subcorticales (e.g., amígdala, hipocampo) 11,12 , cerebelo 10 , y otros órganos como la placenta 13 , sobre todo, a la luz del desarrollo de la epigenómica [14][15][16] .…”
Section: Introductionunclassified
“…In South African, children with fetal alcohol syndrome had altered methylation at imprinted genes compared with healthy children (13). In the Democratic Republic of Congo, maternal stress from ongoing war was associated with differential methylation – including at key genes involved in stress response – among newborns and their mothers (1416). While these studies are providing needed insight into epigenetically labile regions of the genome and key environmental factors in African populations, they only stem from three major study populations in rural Gambia, South Africa, and the eastern Democratic Republic of Congo.…”
Section: Introductionmentioning
confidence: 99%